2022
DOI: 10.3390/molecules27051695
|View full text |Cite
|
Sign up to set email alerts
|

Improved Wound Healing by Naringin Associated with MMP and the VEGF Pathway

Abstract: This study aims to investigate the wound-healing effectiveness of the phenolic compound, naringin, both in vitro and in vivo. Male mice were shaved on their dorsal skin under isoflurane, a biopsy punch was made in four symmetrical circular resection windows (6 mm) to induce a wound. These excision wounds were used to study the topical effects of naringin in terms of various biochemical, molecular, and histological parameters. We observed a significant recovery in the wound area. Increased levels of MMP-2, 9, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Skin wound injuries are common and can lead to severe complications if not treated properly. Naringin can accelerate wound healing by upregulating the expression of growth factors (VEGF-A, B, C, and VEGF-R3) [ 159 ]. In addition, inhibiting NF-κB and COX-2 by topical application of naringin hydrogels enhances the repair and regeneration of deep dermal wounds [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Skin wound injuries are common and can lead to severe complications if not treated properly. Naringin can accelerate wound healing by upregulating the expression of growth factors (VEGF-A, B, C, and VEGF-R3) [ 159 ]. In addition, inhibiting NF-κB and COX-2 by topical application of naringin hydrogels enhances the repair and regeneration of deep dermal wounds [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…EGF expedites wound regeneration in various tissues, including skin, through promotion of endothelial cell and fibroblast proliferation ( Jeong et al, 2020 ). VEGF serves as a multi-functional growth factor, manifesting the capacity to induce angiogenesis ( Yen et al, 2022 ). Specifically, VEGF-α is the most potent angiogenic factor known to date ( Vannella and Wynn, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that upregulation of MMP2 and MMP9 can improve wound healing. 29,30 We speculated that the reason for this discrepancy lies in the different research stages of wound healing. In the proliferation stage, the increase of MMPs can promote the proliferation and migration of cells, and accelerate the formation of angiogenesis and granulation tissue on the wound.…”
Section: Discussionmentioning
confidence: 99%